Transition metal-mediated donor–acceptor coordination of low-oxidation state Group 14 element halides. Issue 14 (16th September 2015) - Swarnakar, Anindya K.; Ferguson, Michael J.; McDonald, Robert; Rivard, Eric
Abstract : The main group element triggered C–H bond activation of a Rh-bound Cp ligand is reported. The key aspect of this transformation is the presence of a highly Lewis acidic Group 14 element site. Abstract : The reactivity of tungsten carbonyl adducts of Group 14 element (Ge, Sn and Pb) dihalides towards the metal-based donors (η 5 -C5 H5 )Rh(PMe2 Ph)2 and Pt(PCy3 )2 was examined. When (η 5 -C5 H5 )Rh(PMe2 Ph)2 was treated with the Lewis acid supported Ge(ii ) complex, THF·GeCl2 ·W(CO)5, cyclopentadienyl ring activation occurred, whereas the analogous Lewis acidic units SnCl2 ·W(CO)5 and PbCl2 form direct adducts with the Rh complex to yield Rh–Sn and Rh–Pb dative bonds. Attempts to prepare metal coordinated element(ii ) hydrides by adding hydride sources to the above mentioned rhodium–E(ii ) halide complexes were unsuccessful; in each case insoluble products were formed along with regeneration of free (η 5 -C5 H5 )Rh(PMe2 Ph)2 . In a parallel study, ECl2 ·W(CO)5 (E = Ge or Sn) groups were shown to participate in E–Cl oxidation addition chemistry with (Cy3 P)2 Pt to give the formal Pt(ii ) complexes ClPt(PCy3 )2 ECl·W(CO)5 .